Singularities of wavefields and sonic boom - Kaouri, K; Awright, D; Chapman, C; Ockendon, J (2008)
This paper analyses the generic singularities that can occur in wavefields driven by point acoustic sources moving steadily or accelerating in homogeneous or stratified atmospheres. These situations are unified by the result that the strongest wavefields satisfy the Tricomi equation, except in cases of very strong focusing of acoustic rays. The implications for sonic boom carpets are discussed. © 2007 Elsevier B.V. All rights reserved.